Transition Metal Dichalcogenide for High-Performance Electrode of Supercapacitor - Muzakir, Saifful Kamaluddin; Samsudin, Ahmad Salihin; Sahraoui, Bouchta (Makara Journal of Technology, 2018)
Molybdenum dichalcogenides have been reviewed from the perspectives of bandgap, conductivity, and oxidation states of transition metal. Researchers have concluded that a narrow-bandgap transition metal dichalcogenide with high conductivity could be achieved for the high-performance electrode of a supercapacitor.